Extracutaneous involvement is common and associated with prolonged disease activity and greater impact in juvenile localized scleroderma - Li, Suzanne C; Higgins, Gloria C; Chen, Mallory; Torok, Kathryn S; Rabinovich, C Egla; Stewart, Katie; Laxer, Ronald M; Pope, Elena; Haines, Kathleen A; Punaro, Marilynn; O’Neil, Kathleen M (Rheumatology (Oxford, England), 2021)
Abstract Objective The aim of this study was to evaluate factors associated with extracutaneous involvement (ECI) in juvenile localized scleroderma (jLS). Methods A prospective, multicentre, 6-month observational study was performed. The data collected included disease features, global assessments, and subject symptoms. Bivariate and linear multilevel regression analyses were performed. Results A total of 86 jLS subjects (80% female, 80% Caucasian), median age of disease onset 7.7 years, were evaluated. Most had linear scleroderma or mixed morphea. Of the 86 subjects, 49 (57%) had 125 extracutaneous problems {median 2 [interquartile range (IQR) 1, 3] per subject} from nine organ systems. Most of these subjects had multiple musculoskeletal problems. ECI was associated with more extensive cutaneous involvement, higher number of symptoms, family history of autoimmunity, and ANA and RF positivity. Subjects with ECI had higher scores for physician global assessment of damage (PGA-D), and parental global assessment of disease impact, but not baseline physician global assessment of disease activity (PGA-A). Although subjects with ECI received more MTX and glucocorticoid treatment, they had a slower reduction in PGA-A scores and symptoms over time, suggesting a poorer response to treatment. In logistic regression modelling, female sex had the largest effect on parental impact scores. Conclusion ECI occurred in the majority of subjects with jLS, and was associated with more medication use, longer treatment duration, higher PGA-D scores, and higher parental assessment of disease impact. Our findings suggest that jLS subjects with ECI have greater overall disease burden, both cutaneous and extracutaneous, and poorer response to treatment. More study of the treatment needs of this population is warranted.